Racial Conflict In Lagravenese's Freedom Writers: A Sociological Perspective - Fitriani, Devi (2012)
This study is aimed to show the racial conflict in Freedom Writers movie by using sociological perspective. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociological analysis. This research is qualitative research. Type of data of the study is texts and images taken from two data sources: primary and secondary. The primary data source is Freedom Writers movie directed by Richard LaGravenese. And the secondary data sources are other materials related to the primary data and the social background of American society in the last twentieth and early twenty first century. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the conclusion. Based on the structural analysis, the narrative and the technical elements in this movie are clear. The director delivers a message that real sacrification is useful action for us and others not based on skin color. Based on the sociological analysis, this movie reflects the condition of American society, many fighting and hostility based on the race still happen. The director wants to deliver criticism that government does not have obvious rules to solve the social problem and the society does not have empathy among them selves.